6n+6/9=12

Simple and best practice solution for 6n+6/9=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+6/9=12 equation:


n in (-oo:+oo)

6*n+6/9 = 12 // - 12

6*n+6/9-12 = 0

6*n-34/3 = 0 // + 34/3

6*n = 34/3 // : 6

n = 34/3/6

n = 17/9

n = 17/9

See similar equations:

| 3x-5+7=2x-9 | | 15s^2-8s+1=0 | | 9x+5(35-x)=287 | | 6(3x+1)=3x-9X | | 1/4x+4=y | | y^3=-21 | | -12x+2(x-5)+9x=3x-10 | | x+y=15andx-2 | | -3.5=x/7 | | 8b-9y/4b-b-5y/4b | | b-9y/4b-b-5y/4b | | 8b-9y/4b-b-5y/4b=0 | | 2x^3-1-1=0 | | 20+3m+6m=92 | | -52^1/2 | | 11/2d=8 | | 1/5(10x-4)=7 | | -11/2d | | (4x+15)+(-5+2x)+(-10+6x)=360 | | 144/2 | | -[6z-(17z+9)]=9+(10z+1) | | 0=24x^3+20x^2-54x-45 | | 10+25=-5(9x-7) | | 2x-8y-9x+6y= | | 5x+5=49 | | (x-7)(x^2+10x+16)=0 | | 39x+52-14x-35=5x-13 | | (x-6)(x^2+9x+20)=0 | | 3x=16-1 | | 5x^2+25=-20 | | -16x^2+24x+50=0 | | 0.5(x-1/3) |

Equations solver categories